THE EU URBAN AGENDA CHALLENGES FOR THE BUCHAREST- ILFOV REGION - Liviu RÂNCIOAGĂ (USV Annals of Economics and Public Administration, 2015)
Few months before the Barroso’s mandate completion, the European Commission launched the Communication on an urban dimension of the EU Policies. This one comes to support the achievement of the Europe 2020 Strategy, in the middle of its implementation. The revision of the Strategy is expected in the next spring, and the cities’ fundamental role to reach our common policies objectives is recognized. This is expected to be the key for a more inclusive, sustainable and smarter Europe. The meeting of 28 Mayors of the capital cities of EU on October 1 , 2014 in Rome shows the need to urgently adopt an Urban Agenda of the European Union. The administration of Bucharest strongly supports the initiative and considers as priorities in the coming period: the creation of a data base among the capitals comprising the best practices, making permanent the urban dialogue by creating a platform allowing and encouraging citizens’ involvement in the decision-making actions, the promotion of the success examples and strengthening the experience exchange in the context of the similarity of the problems the current society is confronted with. Meanwhile the subsidiarity is expected to be respect and a large part of European investments available over the next 7 years will be allocated to strategic targets concerning research, innovation and promotion of the small and medium enterprises.